PUBLIC SECTOR LEADERSHIP IN LICENSING DIVISIONS - Hartono, Setyo; Zauhar, Soesilo; Haryono, Bambang Santoso; Domai, Tjahjanulin; Muslim, Abd. Qadir (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Public Sector Leadership related to a leader’s capability to actualize an effective organization and could give a good motivation towards work performance in order to create a better quality of public service. Factors that can boost and increasing the work performance, which are: leader commitment, leadership style, changes in organization culture and work plan. The goal of this research is to find, understanding, explaining and processing view about public sector leadership in improving sevices of Permit Division at Bojonegoro Regency but also understanding the supporting and hindering factors in it. The research shows that the concept of Public Sector Leadership can increase the services in Permit division at Bojonegoro Regency optimally. This shows with the leader commitment, leadership commitment and organization culture that integrated in work space and also the existence of a correct work plan. But, there is also supporting and hindering factors that can affect the performance and quality of services in Permit Division of Bojonegoro Regency. Moreover, performance of public sector employee were reviewed through productivity concept, responsiveness, responsibility, accountability and service quality. Thus, it can be known that Public Sector Leadership is a concept that can be a guidelines to increase the quality of public services, in example like Permit Division of Bojonegoro Regency.